Diversity and distribution of tick species (Acari: Ixodidae) associated with human otoacariasis and socio-ecological risk factors of tick infestations in Sri Lanka - Ariyarathne, S.; Apanaskevich, D.A.; Amerasinghe, Priyanie H.; Rajakaruna, R.S. (Springer, 2016)
Tick infestation in humans is a major public health concern. The diversity and distribution of tick species associated with human otoacariasis was studied in five districts: Anuradhapura, Kandy, Kurunegala, Nuwara Eliya and Ratnapura in the main agro-climatic zones of Sri Lanka. Ticks from patients attending the ear, nose and throat clinics of the General Hospitals were collected during a 3 year period. In total 426 ticks were collected. Most human otoacariasis cases were reported from Kandy (33.8 %) and the fewest from Nuwara Eliya (8.2 %). Of the five tick species identified, nymphs of Dermacentor auratus constituted 90.6 % of the collection. Rhipicephalus sanguineus, Hyalomma isaaci, Haemaphysalis bispinosa and Otobius megnini were found rarely infesting humans possibly as an accidental host; H. bispinosa and O. megnini in the human ear canal were first time records in Sri Lanka. Females and children under 10 years were identified as risk groups of human otoacariasis. Subsequently, a field study was carried out to determine socio-ecological risk factors of human tick infestations in the five districts. Based on hospital data, eight villages with high prevalence of otoacariasis were selected from each district. A total 40 villages were visited and 1674 household members were interviewed. Involvement in outdoor activities, presence of wild animals around the house, location of the house in close proximity to a forest and occupation were identified as major risk factors.